"Top‐Down" Li Deposition Pathway Enabled by an Asymmetric Design for Li Composite Electrode. Issue 35 (2nd August 2019) - Yue, Xin‐Yang; Li, Xun‐Lu; Bao, Jian; Qiu, Qi‐Qi; Liu, Tongchao; Chen, Dong; Yuan, Shan‐Shan; Wu, Xiao‐Jing; Lu, Jun; Zhou, Yong‐Ning
Abstract: Designing Li composite electrodes with host frameworks for accommodating Li metal has been considered to be an effective approach to suppress Li dendrites. Herein, an asymmetric design of a Mo net/Li metal film (MLF) composite electrode is developed by an inverted thermal infusion method. The asymmetric MLF electrode has a dense oxide passivated layer on the top side, a porous Mo net matrix on the back side, and active Li layer in between. The back side has a larger specific area and higher electric field than the top side, which contacts with the separator upon cycling, triggering the preferred Li deposition and stripping of the porous back side of the electrode far from the separator. The surface passivation layer on the top side of the electrode as an artificial solid electrolyte interphase ensures the stable contact with the electrolyte and separator. Meanwhile, the porous structure of the supporting Mo net provides enough space for accommodating the volume change during Li deposition and stripping. This asymmetry design enables a unique "top down" growth pathway for Li deposition in the MLF electrode, suppressing the dendrite growth effectively. The design strategy provides a new direction for high‐energy dendrite‐free Li metal anodes. Abstract : An asymmetric Mo net/Li metal film (MLF) composite electrode with a thickness of 90 µm is designed and fabricated by an inverted thermal infusion method. This MLF electrode enables a unique "top‐down" growth pathway for Li deposition, suppressing the dendrite growth effectively and ensuring promising electrochemical performance.